Entisol Chemical Properties on the System Organic Agriculture - Renaldo Olivier (GoAcademica Research & Publishing, 2020)
Agricultural systems based on high input energy materials (fossil materials) such as chemical fertilizers and pesticides can damage soil properties and will ultimately reduce soil productivity in the future. Alternative agricultural systems that use low input energy (low input energy) are believed to be able to maintain soil fertility and environmental sustainability while at the same time maintaining or increasing soil productivity. Organic farming systems prioritize the use of organic materials and waste recycling. This research reveals how changes have taken place in the physical and chemical properties of soils that have carried out organic farming systems for several times. The study uses a sampling method on farmer’s land that has been studied to treat organic and non-organic farming systems. Two soil samples were taken from 2 different locations to represent soil organic farming systems and 4 soil samples were taken from 4 different locations representing non-organic farming systems. Soil sampling was carried out at a depth of 20 cm. The results showed significant differences in the chemical properties of the soil (CEC, pH H2O, available P, available K, total N, carbon content, humic acid and fulfat) between the soil with organic and inorganic farming systems which showed better values ​​in the agricultural system organic.